2020
DOI: 10.3390/membranes10040062
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Bridgehead Methyl Substituents on the Gas Permeability of Tröger’s-Base Derived Polymers of Intrinsic Microporosity

Abstract: A detailed comparison of the gas permeability of four Polymers of Intrinsic Microporosity containing Tröger’s base (TB-PIMs) is reported. In particular, we present the results of a systematic study of the differences between four related polymers, highlighting the importance of the role of methyl groups positioned at the bridgehead of ethanoanthracene (EA) and triptycene (Trip) components. The PIMs show BET surface areas between 845–1028 m2 g−1 and complete solubility in chloroform, which allowed for the casti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 46 publications
0
22
0
Order By: Relevance
“…On the other hand, when the alkyl groups at the bridge heads are changed from hydrogen groups (=no substituent, 47 ) ([ 59 ]) to bigger methyl groups ( 53 ), ref. [ 64 ] both P O 2 and α decrease at the same time. The small substituents may fill the original micropores.…”
Section: Macromolecular Design For Oxygen/nitrogen Permselective Membranes—top-performing Polymersmentioning
confidence: 96%
See 1 more Smart Citation
“…On the other hand, when the alkyl groups at the bridge heads are changed from hydrogen groups (=no substituent, 47 ) ([ 59 ]) to bigger methyl groups ( 53 ), ref. [ 64 ] both P O 2 and α decrease at the same time. The small substituents may fill the original micropores.…”
Section: Macromolecular Design For Oxygen/nitrogen Permselective Membranes—top-performing Polymersmentioning
confidence: 96%
“…After we had reviewed the data until 2013 and summarized them as described in 2.1, we then thoroughly searched for reports published from 2014 to the present and renewed the plots for top-performing polymers from the previous plots until 2013 ( Figure 3 ) to the latest plots ( Figure 6 ) of polymers showing the highest α at each P O 2 reported until 2020. The values and categorization are listed in Table 4 [ 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 ]. The chemical structures of these polymers showing the best performances are shown in Chart 4 .…”
Section: Macromolecular Design For Oxygen/nitrogen Permselective Membranes—top-performing Polymersmentioning
confidence: 99%
“…The H 2 -permselectivities of the composite membrane measured in this study were briefly compared with those recently reported for other membranes composed of various materials systems, and their H 2 permeation data with α(H 2 /X) (X = N 2 (0.364 nm) [ 51 ] or O 2 (0.346 nm) [ 51 ]) measured under the dry condition at T ≤ 50 °C are listed in Table 3 [ 18 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 ]. Among them, novel ultrathin (9 nm thickness) graphene oxide membrane formed on an anodic oxidized alumina support (#09) exhibited a H 2 permeance of approximately 1 × 10 −7 mol m −2 s −1 Pa −1 with α(H 2 /N 2 ) of 900 at 20 °C [ 75 , 76 ].…”
Section: Resultsmentioning
confidence: 99%
“…Other notable recent studies investigated the effects of 1) 9,10‐bridgehead substitution in ethano (EA) and triptycene (Trip) building blocks [ 98 ] and 2) 2,6‐ and 2,7‐isomerism in the triptycene repeat unit [ 99 ] on the gas permeation properties of TB‐derived ladder polymers. Malpass‐Evans et al (2020) studied the effects of bridgehead substitution on gas permeability and selectivity of ethanoanthracene‐ and triptycene‐based TB ladder polymers (PIM–Trip–TB and PIM–EA–TB).…”
Section: Development Of Novel Pim Materialsmentioning
confidence: 99%
“…Malpass‐Evans et al (2020) studied the effects of bridgehead substitution on gas permeability and selectivity of ethanoanthracene‐ and triptycene‐based TB ladder polymers (PIM–Trip–TB and PIM–EA–TB). [ 98 ] In the case of PIM – EA – TB film samples aged for ≈100 days, 9,10‐methyl substitution in PIM–EA(Me2)–TB did neither result in significant changes in gas permeability nor selectivity compared to the unsubstituted ladder PIM–EA(H 2 )–TB (Table 1), that is, O 2 permeability values of aged PIM–EA(Me 2 )–TB and PIM–EA(H 2 )–TB were 933 and 902 Barrer with O 2 /N 2 selectivities of 5.0 and 4.8, respectively. [ 98 ] In the case of aged PIM – Trip – TBs it appears that 9,10‐methyl‐substitution decreased both gas permeability and gas‐pair selectivity (Table 1)—however, a fair comparison between PIM–Trip(Me 2 )–TB aged for 102 days and PIM–Trip(H 2 )–TB aged for 407 days may be premature as the aging periods between the permeation measurements differed significantly.…”
Section: Development Of Novel Pim Materialsmentioning
confidence: 99%